2008
DOI: 10.1007/s11064-008-9845-z
|View full text |Cite
|
Sign up to set email alerts
|

Docosahexaenoic Acid Significantly Stimulates Immediate Early Response Genes and Neurite Outgrowth

Abstract: Docosahexaenoic acid (22:6n - 3, DHA) is known to enhance neurogenesis. However, the immediate-early effect of DHA on neurogenesis is not fully elucidated. We studied the effect of DHA supplementation (10 and 30 microM) on morphological and molecular changes at different time points of nerve growth factor (NGF, 50 ng/ml)-induced differentiation of PC12 (pheochromocytoma) cells. Cells were analyzed throughout the differentiation process (2 h, 1, 2, 3, 4, and 10 days), for neurite outgrowth (light microscopy and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 36 publications
0
25
0
Order By: Relevance
“…These discrepancies may be due to differences in the extent of AD pathology, genotype signature or a combination of genetic and environmental variables. Although the functional consequences of DHA-mediated increases in hippocampal drebrin remain unknown, DHA potentiates synaptic transmission, improves synaptic protein quantity, activates dendritic spine plasticity (Cansev et al, 2008), protects against loss of drebrin and its binding partner actin (Calon et al, 2004), and induces neurogenesis (Dagai et al, 2008; Venna et al, 2008). By contrast, cortical synaptotagmin levels were upregulated in APPswe/PS1ΔE9 tg female mice fed DHA compared to female tg mice fed control diet.…”
Section: Discussionmentioning
confidence: 99%
“…These discrepancies may be due to differences in the extent of AD pathology, genotype signature or a combination of genetic and environmental variables. Although the functional consequences of DHA-mediated increases in hippocampal drebrin remain unknown, DHA potentiates synaptic transmission, improves synaptic protein quantity, activates dendritic spine plasticity (Cansev et al, 2008), protects against loss of drebrin and its binding partner actin (Calon et al, 2004), and induces neurogenesis (Dagai et al, 2008; Venna et al, 2008). By contrast, cortical synaptotagmin levels were upregulated in APPswe/PS1ΔE9 tg female mice fed DHA compared to female tg mice fed control diet.…”
Section: Discussionmentioning
confidence: 99%
“…In young rats, the administration of DHA leads to an improved learning ability [98]. Additionally, DHA is involved in neuronal differentiation [99], neurogenesis [100], and protection against synaptic loss [101]. Therefore, DHA is discussed to be involved in pathological processes of AD.…”
Section: Docosahexaenoic Acid and Alzheimer's Diseasementioning
confidence: 99%
“…Animal studies have shown that DHA readily crosses the blood/brain barrier (Ouellet et al, 2009) and plays a critical positive role in all aspects of neuronal growth, synaptic connections, and functioning (Cockburn, 1994; Jamieson et al, 1999; Salem et al, 2001; Chang et al, 2009). This includes roles in regulating the activity of Na + K + ATPase in the neural membrane (Bourre et al, 1989; Turner et al, 2003; Kumosani et al, 2011), neuron size (Ahmad et al, 2002), neurogenesis (Auestad and Innis, 2000; Coti Bertrand et al, 2006; Beltz et al, 2007; Novak et al, 2008; Da Costa et al, 2009; Dagai et al, 2009; He et al, 2009), neurite growth (Calderon and Kim, 2004; Sakamoto et al, 2007; Liu et al, 2008; Novak et al, 2008; Cao et al, 2009), synapse formation and function (Yoshida et al, 1997; Cansev and Wurtman, 2007; Wu et al, 2008; Cao et al, 2009; Wurtman et al, 2009), neuronal integrity and vitality (Issa et al, 2006; Mukherjee et al, 2007; Niemoller et al, 2009), gene expression in the brain (Kitajka et al, 2002), brain glucose transport (Pifferi et al, 2007), cognitive development (Heinemann and Bauer, 2006; Bongiovanni et al, 2007; Coluccia et al, 2009), and learning ability (Bourre et al, 1989; Yoshida et al, 1997; Greiner et al, 1999; Salem et al, 2001; Takeuchi et al, 2002; Shirai and Suzuki, 2004; Garcia-Calatayud et al, 2005; Lim et al, 2005; Chung et al, 2008; Holguin et al, 2008; Fedorova et al, 2009; He et al, 2009; Hooijmans et al, 2009; Jiang et al, 2009). …”
Section: Introductionmentioning
confidence: 99%